Natural approach in language teaching - Azizova, Makhliyobonu (The Lingua Spectrum, 2025)
The article is devoted to the natural approach which belongs to a tradition of language teaching methods based on observation and interpretation of how learners acquire both first and second languages in non-formal settings. Such methods reject the formal (grammatical) organization of language as a prerequisite to teaching. They hold with that an adult can effectively be taught by grammatically unordered materials and that such an approach is, indeed, the only learning process which we know for certain will produce mastery of the language at a native level. In the Natural Approach, a focus on comprehension and meaningful communication as well as the provision of the right kinds of comprehensible input provide the necessary and sufficient conditions for successful classroom second and foreign language acquisition. This has led to a new rationale for the integration and adaptation of techniques drawn from a wide variety of existing sources like Communicative Language Teaching. Furthermore, the Natural Approach emphasizes a stress-free environment, learner motivation, and practical activities that encourage gradual language development. It values authentic input and interaction, which are crucial in building communicative competence and long-term retention of language skills.